POSTOPERATIVE ABNORMALITIES OF INTESTINE AND FACILITIES OF IT'S CORRECTION IN CHILDREN WITH ANORECTAL MALFORMATION - U.Sh. Karimov; A.I. Lenushkin (Вопросы современной педиатрии, 2007)
In abstract the authors represent the observation after 114 patients in age from 1 till 14 years passing the treatment last 15 years. All of them were been operated in cause of an rectal abnormality and suffering by dysfunction of terminal part of intestine and unsuccessful treatment of medics of different specification. Authors developed the principles of treatment accounting peculiarity and type of dysfunction, which noticeably improve the results of treatment.Key words: congenital abnormality of an rectal zone, motility disturbances of large intestine, children.